Synthetic mRNA Encoding VEGF-A in Patients Undergoing Coronary Artery Bypass Grafting: Design of a Phase 2a Clinical Trial - Vesa Anttila; Antti Saraste; Juhani Knuuti; Pekka Jaakkola; Marja Hedman; Sara Svedlund; Maria Lagerström-Fermér; Magnus Kjaer; Anders Jeppsson; Li-Ming Gan (Cell Press, 2022)
Therapeutic angiogenesis may improve outcomes in patients with coronary artery disease undergoing surgical revascularization. Angiogenic factors may promote blood vessel growth and regenerate regions of ischemic but viable myocardium. Previous clinical trials of vascular endothelial growth factor A (VEGF-A) gene therapy with DNA or viral vectors demonstrated safety but not efficacy. AZD8601 is VEGF-A165 mRNA formulated in biocompatible citrate-buffered saline and optimized for high-efficiency VEGF-A expression with minimal innate immune response. EPICCURE is an ongoing randomized, double-blind, placebo-controlled study of the safety of AZD8601 in patients with moderately decreased left ventricular function (ejection fraction 30%–50%) undergoing elective coronary artery bypass surgery. AZD8601 3 mg, 30 mg, or placebo is administered as 30 epicardial injections in a 10-min extension of cardioplegia. Injections are targeted to ischemic but viable myocardial regions in each patient using quantitative 15O-water positron emission tomography (PET) imaging (stress myocardial blood flow < 2.3 mL/g/min; resting myocardial blood flow > 0.6 mL/g/min). Improvement in regional and global myocardial blood flow quantified with 15O-water PET is an exploratory efficacy outcome, together with echocardiographic, clinical, functional, and biomarker measures. EPICCURE combines high-efficiency delivery with quantitative targeting and follow-up for robust assessment of the safety and exploratory efficacy of VEGF-A mRNA angiogenesis (ClinicalTrials.gov: NCT03370887).